2018
DOI: 10.1021/acs.jchemed.8b00200
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective Wireless Microcontroller for Internet Connectivity of Open-Source Chemical Devices

Abstract: This paper presents a system for remote monitoring of turbidity data that can detect light intensity and temperature using a microcontroller and the Internet of Things. It comprises a light dependent resistor and infrared temperature sensor interfaced with an ESP-12E microcontroller, a programmable data acquisition platform which together enable remote real-time monitoring of turbidity data applicable to chemical education. This system will allow educators and students to guide and monitor chemical experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Mercer et al . demonstrated that a cost-effective device could be produced using Internet of Things (IoT) connected microcontrollers that could log turbidity data 8 . While insight gained into the precipitation of NaCl from Na 2 S 2 O 3 and HCl was useful in the context of chemical education, insight gained from this type of measurement may also be of interest to scientists studying novel systems.…”
Section: Introductionmentioning
confidence: 99%
“…Mercer et al . demonstrated that a cost-effective device could be produced using Internet of Things (IoT) connected microcontrollers that could log turbidity data 8 . While insight gained into the precipitation of NaCl from Na 2 S 2 O 3 and HCl was useful in the context of chemical education, insight gained from this type of measurement may also be of interest to scientists studying novel systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this communication we report on control of microfluidic flow and direction using inexpensive mass‐produced components: the Arduino Uno microcontroller, high torque servos, a commercial syringe pump and electronically commutated motors. Use of a microcontroller, instead of desktop or laptop, is a route towards miniaturisation, integration and automation of immunoassay protocols, identified as goals previously . The microcontroller can implement custom protocols and sequencing events in a rapid and simple manner using high‐level programming language C/C++.…”
Section: Figurementioning
confidence: 99%
“…To this end, the iMED uses over the air updates (OTA) mechanism which allows the potentiostat to update itself based on data received while the normal firmware is running (for example, over WiFi). The device also sends all electrochemical data to an open-source cloud-based server for data post-processing [41]. This data is then visualised and accessible via any Internet connected device, such as a smart phone, tablet, laptop or wearable.…”
Section: Introductionmentioning
confidence: 99%